IoT-enabled user agency for building sustainability - Lee, Stephen; Dieng, Ousmane; Shangguan, Longfei; Biehl, Jacob; Lee, Adam; Mossé, Daniel; Chrysanthis, Panos K. (Frontiers in the Internet of Things, 2023)
Buildings are a significant source of greenhouse gas emissions, and many organizations recognize that reducing commercial building-related emissions is crucial to achieving a carbon-neutral future. However, leveraging state-of-the-art building energy-efficiency techniques can be expensive and require installing new equipment, resulting in only a small percentage of energy-efficient commercial buildings. To address this challenge, our paper focuses on empowering building occupants to become informed change-makers that drive building efficiency through an IoT-based solution. By leveraging the data collected from low-cost sensors, we envision creating personalized dashboards and interventions for individuals, fostering energy transparency and empowering people to optimize their space usage while reducing emissions. Moreover, we can leverage human flexibility and flexible environments to further improve space usage and realize energy and emissions reduction opportunities. Thus, by enabling human-building interaction, our approach will be more effective in achieving the full potential of reducing energy and emissions in existing buildings.